First-line bevacizumab-containing therapy for HER2-negative locally advanced/metastatic breast cancer: Real-world experience from >2000 patients treated in the multicentre AVANTI study. (December 2021) - Müller, Volkmar; Ruhnke, Markus; Hoffmann, Oliver; Grafe, Andrea; Tomé, Oliver; Fett, Werner; Bruch, Harald-Robert; Sommer-Joos, Ann-Katrin; Schneeweiss, Andreas
Abstract: Aim: The multicentre non-interventional AVANTI study assessed safety, effectiveness and patient-reported outcomes with approved first-line bevacizumab-containing regimens for HER2-negative locally recurrent/metastatic breast cancer (LR/MBC) in German routine oncology practice. Methods: Eligible patients had HER2-negative LR/MBC, no bevacizumab contraindications and no prior chemotherapy for LR/MBC. Chemotherapy schedule, diagnostics and follow-up were at physicians' discretion. Data were collected for 1 year after starting bevacizumab, then every 6 months for 1.5 years (maximum follow-up: 2.5 years). Patients and physicians rated treatment satisfaction. Subgroup analyses were prespecified in clinically relevant populations, including triple-negative breast cancer (TNBC). Results: Between November 1, 2009 and April 30, 2016, 2065 eligible patients at 346 centres received bevacizumab with paclitaxel or capecitabine. Patients receiving bevacizumab–capecitabine were less likely to have de novo disease and more likely to have TNBC, age ≥60 years and prior anthracycline/taxane and/or endocrine therapy. Median PFS was 12.6 (95% CI 11.9–13.2) months (12.8 with bevacizumab–paclitaxel, 10.5 with bevacizumab–capecitabine); median OS was 23.9 (95% CI 22.2–25.1) months. Outcomes were worse in patients with TNBC, prior anthracycline/taxane or prior endocrine therapy. Grade ≥3 adverse events occurred in 27% of patients. Treatment was discontinued for adverse events in 15%. Treatment satisfaction was rated as good or better by 304/394 responding patients (77%) at week 54 and in 1393/2065 patients (67%) by physicians overall. Conclusions: In routine clinical practice, effectiveness and safety of first-line bevacizumab-containing therapy for LR/MBC were consistent with experience from phase III trials. Patient and physician treatment satisfaction showed high concordance. Highlights: AVANTI assessed 1st-line bevacizumab-based therapy for LR/MBC in routine practice. Median progression-free and overall survival were 12.6 and 23.9 months respectively. Treatment satisfaction was rated as good or better by 77% of patients at week 54. Physician- and patient-rated treatment satisfaction showed high concordance. Effectiveness and safety were consistent with experience from phase III trials.